An Investigation Into Low Ergonomic Risk Awareness Among Staffs at Early Product Development Phase in Malaysia Automotive Industries - Fazilah, Abdul Aziz; Noraini, Mohd Razali; Nur Najmiyah, Jaafar (2015)
Currently there are many automotive companies still unable to effectively prevent consequences of poor ergonomics in their manufacturing processes. This study purpose is to determine the surrounding factors that influence low ergonomics risk awareness among staffs at early product development phase in Malaysia automotive industry. In this study there are four variables, low ergonomic risk awareness, inappropriate method and tools, tight development schedule and lack of management support. The survey data were gathered from 250 respondents of local automotive companies in Malaysia. The data was analysed through statistical analysis using SPSS software. Study results revealed that low ergonomic risk awareness has influence by inappropriate method and tool, and tight development schedule. Inappropriate method and tools, and tight development schedule showed positive linear relationship with the low ergonomic risk awareness. The more inappropriate method and tools applied; the lower their ergonomic risk awareness. The more tight development schedule is the lower ergonomic risk awareness. However lack of management support does not affect employees low ergonomics risk awareness. The relationship between low ergonomic risk awareness and inappropriate method and tools depends on staff’s age, and education level. Furthermore the relationship between low ergonomic risk awareness and tight development schedule depends on staff’s working experience and number of project involvement. The main contribution of this paper was identified the number of factors of low ergonomics risk awareness and offers better understanding on ergonomics risk awareness among researchers and automotive manufacturer’s employees during product development process.